Avaliação da torrefação e densificação de resíduos agrícolas no Brasil - Silva, Fábio Teixeira Ferreira da (2017)
Brazil is one of the major agricultural producers in the World. This large-scale production leads to a vast amount of residues left in the field, which ultimately carry a considerable potential to produce energy vectors. Nonetheless, the energy usage of this resource face technical and logistical challenges. The torrefaction of biomass converts it into a coal-like product, while the densification concentrates its mass per unit of volume. Hence, these pretreatments simplify the bioenergy supply chain logistics. Therefore, this dissertation aims to develop a methodology to assess the benefits of torrefaction and pelletization to the syngas production from straw supply chain in Brazil. Firstly, it is calculated the primary energy potential of straws from sugarcane, soybean, maize, rice and wheat production, which is afterwards mapped over the Brazilian, determining clusters for each biomass. Then, the gasification process for each straw is simulated with different configurations of the supply chain, leading to different cases of study. Findings indicate a potential of 2.6 EJ in primary energy terms associated with the sum of all straws in Brazil and 214 PJ only for the clusters. Regarding the production chain, findings show that the combination of both torrefaction and pelletization pretreatments reduce substantially the total cost of the straw-based bioenergy supply chain, by allowing higher scales at final conversion and reducing logistical costs, especially on storage.